ASSESSING COMPLIANCE AND BARRIERS IN FUNCTIONAL FEASIBILITY CERTIFICATION OF PUBLIC BUILDINGS: CASE EVIDENCE FROM BANDA ACEH, INDONESIA - Hafnidar Abdul Rani; Tamalkhani Syammaun; Firmansyah Rachman; Jurisman Amin; Andi Fahlevi (Rang Teknik Journal, 2026)
The Functional Feasibility Certificate (SLF) is a legal requirement in Indonesia to ensure that buildings meet safety, health, and usability standards before being occupied, especially for public and commercial facilities. This study investigates the low adoption of SLF in public buildings in Banda Aceh, a mid-sized urban center in Indonesia. A qualitative case study approach was applied, involving direct observation and semi-structured interviews at four purposively selected sites: the BSI Landmark Building, Dr. Zainoel Abidin Regional General Hospital (Polyclinic), Kyriad Muraya Hotel, and Suzuya Mall. Results showed that only one building, the BSI Landmark had a valid SLF certificate. The remaining three lacked critical components such as fire doors, smoke detectors, and evacuation plans, despite the presence of basic safety infrastructure. Thematic analysis revealed three dominant barriers to certification: procedural complexity, limited institutional capacity, and low awareness among building managers. These findings highlight the need for streamlined digital certification systems, improved municipal support, and targeted regulatory outreach. The study contributes to the literature on urban safety governance in Indonesia and offers practical insights for strengthening disaster risk resilience and building compliance frameworks in Indonesian cities. Keywords: Functional feasibility certificate, Public building safety, Building regulation